Penerapan Pendekatan Interpersonal Kepribadian Harry S. Sullivan Dalam Mengatasi Korban Bully - Risydah Fadilah; Nurdelita Anggraini; Nur Anissa; Nidaul Ummah (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
Sullivan viewed human life as an energy system, whose primary concern was how to relieve the tension created by desire and anxiety. Cases of bullying that often occur in the world of education in Indonesia are indeed increasingly concerning. Bullying behavior can hurt students, so they feel unwanted and rejected by their environment. This of course will have an effect on various student activities at school. This study aims to determine the application of Harry S.Sullivan's counseling to overcome bullying victims and feel bad when given responses by other people to students of SMAN 1 Galang. This study uses interview techniques. The method of collecting data is by anamnesis to find out the problems of these students. The subject in this study was one of the 11th grade students of SMAN 1 Galang.